"To szaleńcy tworzą historię". Aleksandros Panagulis w twórczości Oriany Fallaci = "It`s the crazies who make history". Alexandros Panagulis in the works of Oriana Fallaci - Tichoniuk-Wawrowicz, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Greek history is a bloody amalgam. On the one hand it is the cradle of many rich ancient cultures,on the other it is a string of massacres. Between 1967 and 1974 Greece faced a series of right-wingmilitary juntas led by a group of colonels, which caused dissent and resistance from the democraticelements of the Greek society.
Keywords: Fallaci, Oriana (1929-2006); Panagulis, Aleksandros (grecki polityk; 1939-1976); literatura włoska; biografie; 20 w.